ANALYSIS OF PROVERBS RELATED TO THE CATEGORY OF MORAL EVALUATION IN ENGLISH FOLKLORE - Makhkamova, M.A. (QO‘QON UNIVERSITETI XABARNOMASI, 2026)
This article explores English proverbs that serve as vessels of moral assessments, thus shedding light on the ethical values, societal standards, and cultural ideals found in traditional English folklore. By categorizing and analyzing selected proverbs, the study illustrates how moral evaluations are embedded in language and culturally passed down through generations. Utilizing the theoretical perspectives of cultural linguistics and axiological linguistics, the research underscores how proverbs serve as markers of values, promoting virtues such as honesty and hard work while denouncing vices like greed and laziness. The article also examines the linguistic and stylistic features that make moral proverbs memorable and persuasive in communication. Particular attention is given to rhetorical devices such as metaphor, parallelism, contrast, rhyme, and alliteration, which enhance the expressive power of proverbs and facilitate their transmission through oral tradition. The study highlights the educational and regulatory functions of proverbs in both traditional and modern contexts, showing how they influence moral consciousness and social behavior. Furthermore, the research emphasizes the relationship between language, culture, and ethical norms, demonstrating that proverbs serve as cultural codes that preserve collective wisdom and moral experience. The findings confirm that English proverbs reflect not only individual ethical values but also broader cultural principles such as responsibility, reciprocity, diligence, and social harmony. As a result, proverbs remain an important linguistic resource for understanding the moral worldview embedded in English folklore and cultural communication.